Implementasi Knowledge Management Berbasis Model SECI di Perpustakaan Daerah Provinsi Sumsel - Ummu Farida Muthmainnah; Putri Salsabilah; Zaskia Aulia Wulandari; Talitha Zafirah; Ken Ditha Tania; Zaqqi Yamani A (Universitas Methodist Indonesia, 2026)
This study analyzes the implementation of knowledge management based on the SECI model at the Regional Library of South Sumatra Province. The method used is qualitative with a case study design through a systematic literature review and digital content analysis of the website, OPAC INLISLITE, social media, and the DiarySumsel application. The results show that the implementation of the SECI model has been carried out across its four stages. Socialization is realized through direct services and mobile libraries using 4 mobile units. Externalization is evidenced by the documentation of circulation service Standard Operating Procedures (SOPs). The combination is implemented through the integration of INLISLITE and DiarySumsel, which served 23,946 users. Internalization is reflected in the adoption of digital systems by librarians and users. Supporting factors include technology availability, management commitment, and extensive service coverage. The challenges faced are limited trained human resources, suboptimal technology utilization, and low community information literacy.